Correction to: How far are we? Information from the three decades of ethnomedicinal stud-ies in Thailand - Phumthum, Methee (Ethnobiology and Conservation, 2020)
In the original research Phumthum (2020), the first paragraph in the discussion on page 7 compared the study with the study by Hidyati et al. (2015). The author found that the expression might mislead readers. Therefore, the author changes the entire paragraph as the following paragraph. From the time when ethnobotany had become a recognized academic discipline until now, researchers from several of higher educational institutions have continuously participated the recording of traditional knowledge (Albuquerque et al. 2013). In Southeast Asia, Hidayati et al. (2015) mined ethnobotanical studies from Scopus and Web of Science databases representing 312 publications in which 68 of them were from studies in Thailand. For the ethnomedicinal study, the study reveals 66 publications from Southeast Asian countries. Campos et al. (2016) found that there were high numbers of grey literature citations in ethnobiology and ethnomedicines. This study, therefore, includes more data from grey literature namely student theses and scientific reports and reveals 146 publications for only ethnomedicinal study in Thailand. In light of this information, this change does not affect the conclusion of the article.